Seasonal and socio-demographic patterns of self-reporting major disease groups in north-west Burkina Faso: an analysis of the Nouna Health and Demographic Surveillance System (HDSS) data - Gottlieb-Stroh, Tobias; Souares-Coutant, Aurélia; Bärnighausen, Till; Sié, Ali; Zabre, Somkeita Pascal; Danquah, Ina (BMC public health)
Sub-Saharan Africa (SSA) is facing a rapid growth of non-communicable diseases (NCDs), while communicable diseases still prevail. For rural SSA, evidence for this development is scarce. We aimed at quantifying self-reported major disease groups according to season, and determining the associations with socio-economic factors in rural Burkina Faso.
Gesehen am 30.06.2022